2021
DOI: 10.3389/fimmu.2021.724443
|View full text |Cite
|
Sign up to set email alerts
|

PIV and PILE Score at Baseline Predict Clinical Outcome of Anti-PD-1/PD-L1 Inhibitor Combined With Chemotherapy in Extensive-Stage Small Cell Lung Cancer Patients

Abstract: ObjectivesThe objective of this study is to evaluate whether PIV (Pan-Immune-Inflammation Value) and PILE [a score derived from PIV, lactate dehydrogenase (LDH), and Eastern Cooperative Oncology Group Performance Status (ECOG PS)] can predict clinical outcome of anti-PD-1/PD-L1 inhibitor combined with chemotherapy in patients with extensive-stage (ES) small cell lung cancer (SCLC).MethodsA total of 53 patients with ES-SCLC in the control group of clinical trial (NCT03041311) were included in this study. PIV wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 31 publications
(53 reference statements)
4
23
0
Order By: Relevance
“…Fifteen studies encompassing 4942 patients were included in the meta-analyses [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The available studies were conducted on several tumors, including CRC, melanoma, breast cancer, and non-small cell lung cancer ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies encompassing 4942 patients were included in the meta-analyses [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The available studies were conducted on several tumors, including CRC, melanoma, breast cancer, and non-small cell lung cancer ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated both patients treated with immunotherapy (nivolumab and pembrolizumab alone) and targeted therapy with BRAF inhibitors/MEK inhibitors, and separate data for these treatment types were included in the subgroup analyses [ 32 ]. Ten studies included Caucasian patients [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 48 ], while five studies were conducted in the Far East [ 44 , 45 , 46 , 47 , 49 ]. Most studies had a low risk of bias according to the NOS ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PIV includes four CBC-based parameters: neutrophil, platelet, monocyte, and lymphocyte counts. In several studies including malignancies, such as metastatic CM, colorectal carcinoma and non-small cell lung carcinoma, PIV was independently associated with overall survival and progression-free survival (Fucà et al 2020 ; Corti et al 2021 ; Fuca et al 2021 ; Zeng et al 2021 ). Although biomarkers of systemic inflammation including NLR and PLR, have been investigated in patients with MCC, PIV has not yet been studied in this rare malignancy (Zaragoza et al 2016b ; Garnier et al 2018 ; Naseri et al 2020 ; Nghiem et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…PIV has been shown as a prognostic marker in HER-2 (+) breast cancer (14). High PIV (> median) was reported to be correlated with poor clinical outcomes in patients with small cell lung cancer (15). Fucà et al reported that, compared with SII, PIV was superior in evaluating progression-free survival and overall survival in patients with metastatic CRC (16).…”
Section: Introductionmentioning
confidence: 99%